A New Approach to Receipt-Free E-Voting - Jivanyan, A. (Mathematical Problems of Computer Science, 2021)
In this paper we introduce a new electronic voting protocol with provable security properties. The generic method of voting presented here allows choosing different approaches for ballot casting to provide the most user-friendly interface.